The Role of Local Culture in Shaping Social Justice Practices in Multicultural Societies - Sukarni, Sukarni; Nurhayati, Dina; Hasan, Arifin (Journal Social Humanity Perspective, 2024)
This paper analyses how local culture helps to instigate social justice in the multicultural societies with special concern on the intersection of culture systems with the contemporary system of governance. Although the traditional body of management thought tends to view justice in terms of universalized principles, this study shows how justice is defined and practiced in diversified ways, relative to cultures. The qualitative research methodology is based on interviews, observations, and the study of documents, which were used to answer the question of how local traditions, norms, and practices affect the perceptions of fairness, legitimacy, and inclusion in various communities. Results indicate the local culture is both an advantage and an obstacle in the execution of justice. On the one hand, it gives a sense of legitimacy and creates trust by culturally resonant practices of consensus-building, dialogue, and restorative practices. On the contrary, cultural traditions can reproduce exclusions or contradict international standards of equity and rights. The paper also finds the convergence of cultural and modern systems of justice in the form of hybrid modes of governance whereby organizations and societies can negotiate the tensions between tradition and universality. The management implications are far reaching: leaders and institutions need to transcend procedural justice systems to culturally infused and reflexive and participatory practices. This study has made contributions on the management research by not only contributing to the body of research on justice as a culturally mediated concept but also offers implications that can be of great use to policymakers and organizations aiming to work in a culture sensitive and ethical manner. Finally, the paper suggests that there is a need to shift management practices towards dialogical, hybrid and inclusive visions of justice which acknowledge the constitutive practice of culture in determining sustainable social outcomes.